Pengaruh Likuiditas dan Solvabilitas Terhadap Nilai Perusahaan dengan Profitabilitas Sebagai Intervening - Agnes Tamara Indira; Basuki Toto Rahmanto (UNIVERSITAS KALBIS, 2022)
The purpose of this study was to determine the effect of liquidity and solvency on firm value with profitability as an intervening.. Using the population of consumer goods listed on the IDX in 2016-2020. The sampling technique used in this study is purposive sampling with a total of 125 observations on consumer goods companies sector. The analytical technique used in this research is Multiple Linear Regression and path analysis. The hypothesis is accepted if the probability value is 0.05. The results of this study indicate that: (1) liquidity has no effect on firm value, (2) solvency has no effect on firm value, (3) liquidity has no effect on profitability, (4) solvency has no effect on profitability, (5) profitability has no effect on profitability. on firm value, (6) profitability does not mediate liquidity on firm value, (7) profitability does not mediate solvency on firm value.